Household Food Security of Copra Processing Farmers in Northeast Wawonii District, Konawe Islands Regency - Sitti Rosmalah; Hartati Hartati; Harianti Harianti; Nurmaya Nurmaya (Jurnal Ilmu Pertanian Indonesia, 2026)
Food security is a significant priority for the Konawe Islands Regency government. Kendari City, the island's outermost area, serves as the economic center for the inhabitants. The majority of garden or agricultural goods are sold beyond the island, and residents' necessities, such as food and domestic equipment, are met elsewhere. Under these conditions, achieving food security is critical to improving one's quality of life. Most of the Regency's population works as coconut farmers because coconut is a valuable product in this archipelago. This study examined the household food security of copra processing producers in the Northeast Wawonii District. Household food security for copra processing producers on the island was assessed using the Household Food Insecurity Access Scale (HFIAS). The HDDS (Household Dietary Diversity Score) approach was used to assess the diversity of food consumption among the household farmers. Copra processing farmer households in the district had 80% food security. In contrast, they consume rice, fish, oil, sugar, and spices, the majority of which are sourced locally due to the difficulty of accessing markets beyond the island.Keywords: household food insecurity access scale, household dietary diversity score, food security, Konawe Island, Northeast Wawonii